Rational molecular design of electrochromic conjugated polymers: Toward high-performance systems with ultrahigh coloration efficiency - In, Ye Ryeong; Han, Ji Min; Kwon, Ji Eon; Kim, Bong-Gi; Moon, Hong Chul (Elsevier BV, 2022)
Organic electrochromic devices (ECDs) based on pi-conjugated polymers (CPs) have notable advantages including relatively fast switching time and abundant colors with wide tunability. However, their practical applications are still limited due to low coloration efficiency and poor long-term stability. Here, we propose a series of reasonably designed CPs for high-performance ECDs. The principle of molecular design includes the introduction of a fused aryl amine (e.g., indolocarbazole or indoloindole) to effectively modify the optical and electrical characteristics of CPs, leading to high redox stability with fast response and high coloration efficiency (eta). The resulting ECD with the fluorinated indoloindole-based CP exhibits the highest overall performance with rapid coloration and bleaching dynamic responses of -5.6 and -0.6 s, respectively, a large transmittance contrast of -46%, an outstanding eta of-1563.3 cm(2)/C, and a reliable operation stability with an initial transmittance loss of less than 0.6% even after 6,500 cycles. We elucidate the origin of this superb performance by calculating redox rate constants of each CP via the Nicholson method and determining their thin film crystalline structures using grazing-incidence X-ray diffraction. In addition, the ultrahigh cyclic stability is explained by predicting the degree of molecular distortions of CPs during redox reactions through density functional theory.